Quantifying Okun's Leaky Bucket: The Case of Progressive Childcare Subsidies - David Koll; Dominik Sachs; Fabian Stürmer-Heiber; Hélène Turon (CESifo GmbH, 2024)
We formalize and estimate the dynamic marginal efficiency cost of redistribution (MECR) in the spirit of Okun's “leaky bucket” to compare the MECR of an income-contingent childcare subsidy program and of the income-contingent tax and transfer schedule. We set up a dynamic structural model of heterogeneous households choosing their childcare demand and maternal labor supply. Allowing for the availability of informal childcare and for consumption of leisure, we estimate this model within the German context. Our analysis identifies two competing forces. (i) Labor supply responses increase the MECR of the childcare subsidy relative to the tax and transfer system. (ii) Child development effects decrease the MECR of the childcare subsidy relative to the income tax. We show that, under most plausible assumptions on the long-term returns to childcare attendance for children growing up in households of different incomes, progressive childcare subsidies are the more efficient redistribution tool.
Keywords: H23; H31; J13; J22; J24; 330; female labor supply; childcare; family policies; fiscal externalities; dynamic discrete choice; redistribution